The positive role of women in the story of Gilgamesh - Abdullah, Asst.Prof.Dr.Mohammed Amin Ali; Mahmoud, Asst.L.Shanaz Ibrahim (Sulaimani Journal for Humanities, 2026)
In the Sumerian epic of Gilgamesh, women are well-known and valued to the extent that they move from femininity, womanhood and motherhood to divinity, and their roles are transferred from the family and society to the affairs of the state The Sumerian goddess Inanna played a role in the mythology, which led the Sumerians to depict her in various forms, especially as a saint, and later this sanctification in the form of They conveyed to us the sacred texts or the symbols and images of God, or in the form of extraterrestrial beings. Thus, they formulated the idea of female deity and the concept of female sacredness in society The priest and the first speaker, like the mother, became responsible before men for the conditions of life and work, for the soul and for guiding the behavior of others, all of which are reflected in the story of Galgamish. The choice of “The Positive Role of Women in the Story of Gilgamesh” as the title of a paper to be presented at the conference “Women in the Mirror of History” organized by Sulaimani University is an attempt to reflect its level Reflection and interaction of myth and reality of life and showing the positive role of women in Sumerian thought and reality of daily life, is an indication to show the role of myth in directing history It consists of an introduction and two main topics, which are organized as follows: Discussion 1 / Women as goddesses and their positive role in shaping history. Second, women as deified persons and the positive outcome of their discussions. Third: Women as females and their positive role in their social position.
Keywords: Gilgamesh; woman; Enkidu; candle; pub; immortality; advice; hunter; Inanna